Policy network analysis of China's ocean ranching policy: Network structure, actors and interaction. (June 2022) - Yu, Huijuan; Wang, Yezhi; Yin, Wei; Li, Dahai
Abstract: National strategic plans and policies are the important driving forces for the development of ocean ranching in China. Different from the existing research on the evolution of China's ocean ranching policy from the perspective of policy tools and policy performance, this paper focuses on the policy network, actors and their interaction in the process of policy. Through the empirical analysis of 94 policies issued by the State Council and national ministries, and 24 policies from Shandong Province, this study found that not only national and local governments play an irreplaceable role by formulating and implementing relevant policies, but also enterprises, scientific research institutions, social organizations, experts, and the public are actively participating in the policy process so as to express and realize their own interests. These actors cooperate with and have influence on each other, forming a complex network structure with five types of policy networks namely policy community, professional network, intergovernmental network, producer network and issue network, and their interactive relationship. This study also revealed the feature of imbalance in the participation structure, and it is necessary to strengthen the participation and interaction of professional network, producer network and issue network. These conclusions provide useful reference for the improvement of China's ocean ranching policy.